Dynamics of Health, Blue Carbon, and Economic Potential of Mangroves in Muara Gembong: Sentinel-2 and Google Earth Engine Analysis for Food Security and Folu Net Sink 2030 - Jasin, Faisal M.; Anwar, Haerul; Afianti, Ulfa; Purwanto, Anim; Aulia, Rihlah Nur (Program Studi Magister Manajemen Lingkungan, 2025)
Mangroves are vital coastal ecosystems that act as blue carbon sinks, natural barriers against erosion, and economic resources for local communities. However, anthropogenic pressures have caused degradation, including in Muara Gembong, West Java. This study analyzes mangrove health and blue carbon stock dynamics between 2020 and 2025 using Sentinel-2 imagery processed in Google Earth Engine (GEE). Mangrove health was classified using NDVI into three categories: unhealthy, healthy, and very healthy. Aboveground biomass (AGB) was estimated from NDVI-derived models and converted to carbon using a 0.47 factor. Results reveal a decline in healthy mangroves from 87.11 ha to 57.33 ha, while very healthy stands increased from 1,036.15 ha to 1,050.81 ha. Carbon stock decreased by 412 tons, from 11,115 t C (2020) to 10,703 t C (2025). Degradation mainly occurred in transitional zones critical for regeneration. This study highlights the importance of adaptive and integrative mangrove management linking ecological restoration, blue carbon monitoring, and community-based economic initiatives to support Indonesia’s FoLU Net Sink 2030 target.